The Impact of Consumer Attentiveness and Search Costs on Firm Quality Disclosure: A Competitive Analysis - Ghosh, Bikram; Galbreth, Michael R. (Management Science, 2013)
Firms can invest to disclose quality information about their products to consumers, but consumers are not always perfectly attentive to these disclosures. Indeed, technologies such as digital video recorders have increased the ease with which disclosures can be avoided by consumers. Although such inattention may result in a consumer missing information from one or more competing firms, consumers who have missed disclosures might decide to search for quality information to become fully informed before making a purchase decision. In this paper we incorporate consumer attentiveness, as well as the related endogenous search decision, into a model of quality disclosure. Our results suggest that firms should disclose less quality information as the share of partially informed consumers (informed about one firm but not the other) increases, or as consumer search costs increase. We also provide insights into the potential impact of consumer trends toward lower attentiveness and lower search costs. This paper was accepted by J. Miguel Villas-Boas, marketing.